Hak Cipta Aset Nft (Non-Fungible Token): Ancaman Nyata Bagi Seniman - Pramaseta Widiawardana; Rianda Dirkareshza (Jayapangus Press, 2023)
The Non-Fungible Token is an opportunity for artists to introduce their digital works to the general public, but it can also become a real threat to artists' attempts to commercialize their digital arts. This research aims to complement the studies regarding prevention and law enforcement related to copyright infringement of Non-Fungible Token assets. The research method used by the author in this article is normative juridical research supplemented by interviews, and this research uses a statute approach that is carried out by examining all laws and regulations related to the copyright of a work. The Commodity Futures Trading Regulatory Agency cooperates with the Ministry of Communication and Information in terms of prevention by blocking content and data. Another preventive measure is for artists to register with and join the Collective Management Institute (LMK). In addition, special laws and regulations are needed that regulate the protection of Non-Fungible Token assets, as well as the role of copyright law enforcement agencies and the public, to minimize the occurrence of violations in the realm of copyright.